THE VERNACULARIZATION OF SUNNAH: HADITH RECEPTION AND LOCAL IDENTITY IN THE RASULAN TRADITION OF NGALANG VILLAGE - Mh, Syahidil Mubarik; Sakinah, Ekatul Hilwatis (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2026)
It is widely acknowledged that the Rasulan tradition within Javanese society, including in Ngalang, Gunungkidul, represents an expression of gratitude for the harvest, imbued with rich local cultural values. However, the question of how the community receives and integrates the hadith of the Prophet (peace be upon him) into this traditional practice remains underexplored and has not received sufficient scholarly attention. Addressing this issue is crucial for understanding the dynamic relationship between religious texts and local cultural practices within the broader process of Islamization. This study employs a qualitative approach, drawing on field data obtained through observations and interviews with community members and religious figures in Ngalang Village. The data are analyzed using Stuart Hall’s reception theory. The findings reveal three distinct patterns of hadith reception: dominant (13 informants fully accept the values of hadith concerning almsgiving), negotiated (7 informants accept the values of hadith while maintaining mystical elements within the Rasulan tradition), and oppositional (4 informants reject the use of hadith within this context). These variations are influenced by social factors, local cultural frameworks, and religious authority structures that mediate the relationship between hadith texts and the practice of the Rasulan tradition. The findings challenge the assumption that Islamization proceeds in a linear and homogeneous manner; instead, they demonstrate that the integration of hadith values into local traditions is diverse and characterized by negotiation. Therefore, this study contributes to the field of hadith studies and Islamic cultural studies by providing empirical evidence of the role of hadith as an agent of value transformation within local traditional practices. [Sudah menjadi pemahaman umum bahwa tradisi Rasulan di masyarakat Jawa, termasuk di Ngalang, Gunungkidul, merupakan bentuk ungkapan syukur atas hasil panen yang sarat dengan nilai-nilai budaya lokal. Namun, persoalan tentang bagaimana masyarakat meresepsi dan mengintegrasikan hadis Nabi SAW dalam praktik tradisi tersebut masih terbuka dan belum mendapatkan perhatian memadai. Menjawab pertanyaan ini penting untuk memahami dinamika hubungan antara teks keagamaan dan praktik budaya lokal dalam proses islamisasi. Penelitian ini menggunakan pendekatan kualitatif dengan bersumber pada data lapangan berupa observasi dan wawancara terhadap masyarakat serta tokoh agama di Desa Ngalang, yang dianalisis melalui teori resepsi Stuart Hall. Temuan penelitian mengungkap bahwa terdapat tiga pola resepsi terhadap hadis, yaitu dominan (13 informan menerima sepenuhnya nilai hadis tentang sedekah), negosiasi (7 informan menerima nilai hadis namun tetap mempertahankan unsur mistis dalam tradisi Rasulan), dan oposisi (4 informan menolak penggunaan hadis dalam konteks tersebut). Perbedaan ini dipengaruhi oleh faktor sosial, budaya lokal, serta otoritas keagamaan yang memediasi hubungan antara teks hadis dan praktik tradisi Rasulan. Temuan ini menantang asumsi bahwa proses islamisasi selalu berlangsung secara linear dan homogen, dan sebaliknya menunjukkan bahwa integrasi nilai-nilai hadis dalam tradisi lokal berlangsung secara beragam dan negosiatif. Dengan demikian, penelitian ini berkontribusi pada studi hadis dan budaya Islam dengan memberikan bukti empiris tentang peran hadis sebagai agen transformasi nilai dalam praktik tradisi lokal.]